As Paneleiras de Goiabeiras e a dinâmica da Cultura do Barro - Marcelo de Souza Marques; Vinicius de Aguiar Caloti (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2013)

(untitled)
This work will focus on the cultural dynamics of the Paneleiras from Goiabeiras, Vitória – ES, Brazil, and their connections with the political and economic dimensions, reflecting on these social actors, as a professional category and as producers of an immaterial heritage recognized by agencies and their struggle for socioeconomic recognition – aligned with the capitalist logic and the material needs that they have. It was found that the interpretation of the dynamics of the Culture of Clay cannot be restricted to the analysis of isolated pans made by the Paneleiras or of the “place”, but has to put both together as “pan-Paneleiras-place”, as well as its relations with the State's Government, the Municipality, the IPHAN and the economic sphere